Interrupting the Legal Person - Sarat, Austin (Studies in Law, Politics, and Society Ser., 2022)
This special issue is part two of a two-part edited collection on interrupting the legal person, and what this means. Should we think of the legal person as a technical and grammatical question that varies across different legal traditions and jurisdictions? Does this cut across different ways of living and speaking law?